AGRARIAN POTENTIALS IN THE REINDUSTRIALIZATION OF SERBIA - import of inputs and the opportunity costs of development - Milanović, Milan R.; Stevanović, Simo; Dimitrijević, Bojan (Economics of Agriculture, 2016)
After transitional debacles and failures, structural degradation and recession, reindustrialization is imposed as a crucial stage in the economic development of Serbia. The production-market potentials of the agro-complex (as a complex economic subsystem of pre-farm, farm and post-farm activities) and its place in the national economy open the signifcant possibilities of the revitalization of the industries of agrarian inputs (agricultural machines and equipment, mineral fertilizers and pesticides). Considering the structural signifcance of the pre-farm agrarian sector in the Serbian economy, this paper analyzes the fundamental features of production and the foreign-trade exchange, especially the dynamics and changes in the volume and structure of production and the import of agrarian inputs. On that basis, through a target comparative analysis of multi-year data series (1986-2011), the paper explores the trends of production and employment, identifies transitional distortions and the growing import dependence of the Serbian economy and the agro-complex in particular, considers the agrarian potentials in a possible reindustrialization primarily via the revitalization of the industry of agrarian inputs, and highlights a special phenomenon of the opportunity costs of the Serbian agrarian development.